Organizational Culture as a Strategic Mechanism Linking HRM Practices, Transformational Leadership, and Organizational Performance - Christiani, Gladys; Setyawan, Agustinus (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2026)
Manufacturing is a key sector that supports sustainability across other sectors. The performance of manufacturing companies in Batam cannot be separated from the performance of their employees. Employee performance is also influenced by various factors, both internal and external to the Company. The main objective of this research is to scientifically examine the extent to which Organizational Culture, HRM Practices, and Transformational Leadership influence employee training and work discipline toward performance in management. This study employed a quantitative methodology and surveyed manufacturing companies in Batam. Manufacturing: Respondents in this study were 600 employees working in the manufacturing sector in Batam City. The study employs a quantitative design, collecting data from respondents via questionnaires distributed via Google Forms. The number of samples used was 600. The data were processed using SmartPLS 3, and the results indicate that HRM Practices and transformational leadership have a significant positive effect on organizational performance. HRM Practices and transformational leadership are mediated by organizational culture, which has a significant positive effect on organizational performance, as evidenced by employee performance.